2017
DOI: 10.3390/nu9060622
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Management of Skin Health: The Role of Genistein

Abstract: In women, aging and declining estrogen levels are associated with several cutaneous changes, many of which can be reversed or improved by estrogen supplementation. Two estrogen receptors—α and β—have been cloned and found in various tissue types. Epidermal thinning, declining dermal collagen content, diminished skin moisture, decreased laxity, and impaired wound healing have been reported in postmenopausal women. Experimental and clinical studies in postmenopausal conditions indicate that estrogen deprivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 51 publications
0
38
0
7
Order By: Relevance
“…[30] Furthermore, it has been reported to improve skin changes caused by aging. [31] Similar to quercetin and kaempferol, the amount of extracted genistein derivatives depended only on ethanol concentration as quadratic factor (Table 3). It is important to note that in the solutions prepared either with pure water or pure ethanol genistein peak was almost negligible ( Fig.…”
Section: Quercetin Kaempferol and Genistein Derivativesmentioning
confidence: 95%
“…[30] Furthermore, it has been reported to improve skin changes caused by aging. [31] Similar to quercetin and kaempferol, the amount of extracted genistein derivatives depended only on ethanol concentration as quadratic factor (Table 3). It is important to note that in the solutions prepared either with pure water or pure ethanol genistein peak was almost negligible ( Fig.…”
Section: Quercetin Kaempferol and Genistein Derivativesmentioning
confidence: 95%
“…There is some limited evidence in support of this effect (Irrera et al . ). A health claim linking soy isoflavones with the maintenance of skin tonicity was rejected by EFSA as no evidence for a relationship between skin tonicity and skin function was supplied and, therefore, this was not classified a function of the body (EFSA Panel on Dietetic Products Nutrition and Allergies ).…”
Section: Popular Nutraceutical Ingredients and Skin Ageingmentioning
confidence: 97%
“…The authors hypothesised that soy isoflavones may have been responsible for the effects as these compounds are known to bind to estrogen receptors (hence the name phytoestrogens) and as post-menopausal status has been observed to correlate with reduced collagen production in the skin (Stevenson & Thornton, 2007), it is plausible that dietary isoflavones could correct this by mimicking estrogen. There is some limited evidence in support of this effect (Irrera et al 2017). A health claim linking soy isoflavones with the maintenance of skin tonicity was rejected by EFSA as no evidence for a relationship between skin tonicity and skin function was supplied and, therefore, this was not classified a function of the body (EFSA Panel on Dietetic Products Nutrition and Allergies 2011i).…”
Section: Combined Supplementsmentioning
confidence: 99%
“…GE acts as a selective estrogen receptor modulator. Several in vitro and in vivo studies demonstrated the beneficial effects of GE on skin, e.g., for the treatment of keloid scars, stimulation of collagen biosynthesis, acceleration of wound healing or protection of UVB-induced photodamage 147 .…”
Section: Genisteinmentioning
confidence: 99%
“…It has been reported to occur in many plants other than Citrus, such as in the families Fabaceae, Betulaceae, Lamiaceae and Papilionaceae. HE has been reported to possess significant antioxidant, anti-inflammatory, analgesic, immunomodulatory and wound healing effects 147 . Several reports also demonstrated a UVB-protective potential of HE in vitro 151,152 and in vivo 153,154 .…”
Section: Hesperidinmentioning
confidence: 99%